Single Nuclei Sequencing Reveals Novel Insights Into the Regulation of Cellular Signatures in Children With Dilated Cardiomyopathy. Issue 17 (27th April 2021) - Nicin, Luka; Abplanalp, Wesley T.; Schänzer, Anne; Sprengel, Anke; John, David; Mellentin, Hannah; Tombor, Lukas; Keuper, Matthias; Ullrich, Evelyn; Klingel, Karin; Dettmeyer, Reinhard B.; Hoffmann, Jedrzej; et al.
Abstract : Background: Dilated cardiomyopathy (DCM) is a leading cause of death in children with heart failure. The outcome of pediatric heart failure treatment is inconsistent, and large cohort studies are lacking. Progress may be achieved through personalized therapy that takes age- and disease-related pathophysiology, pathology, and molecular fingerprints into account. We present single nuclei RNA sequencing from pediatric patients with DCM as the next step in identifying cellular signatures. Methods: We performed single nuclei RNA sequencing with heart tissues from 6 children with DCM with an age of 0.5, 0.75, 5, 6, 12, and 13 years. Unsupervised clustering of 18 211 nuclei led to the identification of 14 distinct clusters with 6 major cell types. Results: The number of nuclei in fibroblast clusters increased with age in patients with DCM, a finding that was confirmed by histological analysis and was consistent with an age-related increase in cardiac fibrosis quantified by cardiac magnetic resonance imaging. Fibroblasts of patients with DCM >6 years of age showed a profoundly altered gene expression pattern with enrichment of genes encoding fibrillary collagens, modulation of proteoglycans, switch in thrombospondin isoforms, and signatures of fibroblast activation. In addition, a population of cardiomyocytes with a high proregenerative profile was identified in infant patients with DCM but was absent in children >6 years of age. This cluster showed high expression of cell cycle activators such as cyclin D family members, increased glycolytic metabolism and antioxidative genes, and alterations in ß-adrenergic signaling genes. Conclusions: Novel insights into the cellular transcriptomes of hearts from pediatric patients with DCM provide remarkable age-dependent changes in the expression patterns of fibroblast and cardiomyocyte genes with less fibrotic but enriched proregenerative signatures in infants. Abstract : Supplemental Digital Content is available in the text.